2020
DOI: 10.12750/jarb.35.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Porcine somatic cell nuclear transfer using telomerase reverse transcriptase-transfected mesenchymal stem cells reduces apoptosis induced by replicative senescence

Abstract: Somatic cell nuclear transfer (SCNT) is an essential technique in biomedical research for the production of transgenic animals, conservation of endangered species, and establishment of embryonic stem cells (ESCs) (Lee et al., 2014). SCNT has been used to clone diverse animals such as pigs, mice, cattle, and non-human primates (Gouveia et al., 2020). Since pigs are not only favored for mass production but also due to their anatomical and physiological similarities to humans, for the establishment of disease mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the comparison between the two types of MSCs during early and late passages has broadened the scope of understanding the potential applications of these cells based on characteristics such as proliferation rate, differentiation potential, and mitochondrial metabolism. MSCs are very useful cell types that have been used for clinical purposes in animals [ 57 ], humans [ 58 , 59 ], and cultured meat [ 60 ]. Recently, research on fat has gained significance in the field of cultured meat production.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the comparison between the two types of MSCs during early and late passages has broadened the scope of understanding the potential applications of these cells based on characteristics such as proliferation rate, differentiation potential, and mitochondrial metabolism. MSCs are very useful cell types that have been used for clinical purposes in animals [ 57 ], humans [ 58 , 59 ], and cultured meat [ 60 ]. Recently, research on fat has gained significance in the field of cultured meat production.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their unique usefulness, the therapeutic potential has not been consistent, and sometimes no improvement can be seen (Holan et al, 2016;Lohan et al, 2017). Given these difficulties, studies have shown that various chemical, physical, and genetic modification have improved the trophic effects of MSCs, e.g., adhesion, migration, survival, while limiting the senescence during an extended culture period (Jo et al, 2019;Jeon and Rho, 2020;Ocansey et al, 2020). Specifically, unfavorable microenvironment upon being cultured in vitro and being administrated in vivo precludes the clinical uses of cellbased therapeutic products (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%